Age‐dependent accumulation of monoclonal CD4+CD8+double positive T lymphocytes in the peripheral blood of the elderly - Ghia, Paolo; Prato, Giuseppina; Stella, Stefania; Scielzo, Cristina; Geuna, Massimo; Caligaris‐Cappio, Federico (British journal of haematology, 2007)
Summary Multicolour flow cytometric analysis enabled the identification of monoclonal B‐cell lymphocytosis (MBL), frequently resembling chronic lymphocytic leukaemia, at a rather high frequency in peripheral blood (PB) samples from an elderly population. PB T lymphocytes from 103 otherwise healthy subjects >65 years of age and 51 younger donors (<65 years) were analysed. Besides CD4+ and CD8+ single positive (SP) cells, CD4+CD8+ double positive (DP) mature T lymphocytes were present in both series and could be further distinguished into CD4highCD8low and CD4lowCD8high subsets. An age‐dependent increase of both DP T‐cell subsets was observed, while SP T cells remained stable throughout life. Flow cytometry and polymerase chain reaction analysis of the TRBV expression profiles showed the presence of a TRBV restriction within CD4+CD8+ DP cells in more than half (53/103; 55·3%) of the individuals >65 years of age, regardless the actual number of DP T cells observed. Clonal expansions were more prominent within the CD4highCD8low subset, accounting for most circulating DP clones (47/103; 45·6%). A few cases showed more than one (up to three) monoclonal expansion. Clonal CD4lowCD8high DP T‐lymphocyte expansions were detected in only 10/103 samples (9·7%) and showed a close phenotypic similarity to the rare T‐cell large granular lymphocyte leukaemias. The similarities between DP clones and MBL in the elderly may help to better understand the mechanisms of immunosenescence and their relationships with the development of lymphoproliferative disorders.